Paleoceanographic conditions at approximately 20 and 70 ka recorded in Kikaithyris hanzawai (Brachiopoda) shells. (15th October 2017) - Takizawa, Mamoru; Takayanagi, Hideko; Yamamoto, Koshi; Abe, Osamu; Sasaki, Keiichi; Iryu, Yasufumi
Abstract: The δ 13 C and δ 18 O values of fossil brachiopod shells have been widely used as paleoenvironmental proxies. In this study, we investigated intrashell and intraspecific variations in the isotopic and minor element concentrations of well-preserved shells of the brachiopod Kikaithyris hanzawai (Yabe) from the last glacial period (∼20 ka [Last Glacial Maximum; LGM] and ∼70 ka [Marine Isotope Stage 4; MIS4]), collected in the Central Ryukyus, and used these data to estimate the paleoceanographic conditions (seawater temperature, concentration of dissolved inorganic carbon [DIC], and δ 13 C value of DIC [δ 13 CDIC ]). The δ 13 C and δ 18 O profiles along the maximum growth axis, obtained from the inner shell surface, show three distinct intervals, corresponding to changes in shell morphology. These results suggest that the bulk isotopic compositions of brachiopods with complex shell morphologies are unsuitable for paleoenvironmental reconstructions. Nevertheless, there exists a specific shell portion with relatively small intrashell and intraspecific variations. The past seawater temperatures derived from the δ 18 O values of this portion are consistent with the alkenone- and planktic foraminiferal Mg/Ca-based past seawater temperatures reported in previous studies. The past δ 13 CDIC values estimated from the δ 13 C values of the specific shell portion are within the range of the past δ 13 CDIC values calculated from known atmospheric and oceanographic parameters. The past DIC concentrations reconstructed from the brachiopod-based δ 13 CDIC values are lower than the present concentrations in the East China Sea, which can be explained by low partial pressure of CO2 during the last glacial period. These results indicate that the δ 13 C and δ 18 O values obtained from K. hanzawai shells are potential paleoenvironmental indicators. The intrashell and intraspecific variations in the K. hanzawai shells are different for each minor element. Some anomalously high Mn and Fe concentrations in the shells are probably caused by metabolic factor(s), not by meteoric diagenesis. This suggests that the minor element concentrations are useful but not perfect for distinguishing diagenetically altered and unaltered portions of the shells of K. hanzawai in the studied succession.